Mechanisms, strategies and materials in support-free low temperature powder bed fusion - Drummer, Dietmar; Schlicht, Samuel (ANTEC 2025, 2025)
Powder bed fusion processes are among today’s few industrially established additive manufacturing processes. Present power bed fusion process strategies either focus on the application of elevated powder bed temperatures, found in the quasi-isothermal processing of semi-crystalline polymers, or the use of support structures, prevailing in the manufacturing of metals. Motivated by both technological, geometrical, and ecological limitations, cold, support-free processes are required to address intrinsic thermomechanical material properties, such as crystallization shrinkage and thermal shrinkage for minimizing the distortion of manufactured parts. The present contribution provides an overview over existing approaches for the targeted compensation of volumetric shrinkage on the mesoscale. By addressing both mesoscopic phenomena and the macroscale application of scale-invariant processing strategies, we provide insights into the interaction of the melt pool formation and its discrete crystallization, the targeted compensation of thermal shrinkage and material-specific challenges, such as the intermediate occurrence of metastable material phases. Discretized low temperature PBF strategies can be shown to provide the potential for significantly enhancing the additive manufacturing of nucleated and filled materials, high performance thermoplastics as well as to optimize the re-use and facilitated processing of thermoplastic elastomer
Keywords: Powder bed fusion; laser melting; support-free; variothermal; additive manufacturing